Mediator Role of Subjective Well-Being and Job Satisfaction in Relationship Psychological Capital on Career Commitment - Agustini, Tri; Wulansari, Nury Ariani (Universitas Negeri Semarang, 2020)
Abstract Career commitment is motivating force for a person to work in that career continuously, which is based on belief in value of job that has been chosen. Career commitment is influenced by several factors such as psychological capital, subjective well-being, and job satisfaction. This study aims to examine the mediating effect of subjective well-being and job satisfaction in the relationship of psychological capital to career commitment. The population in this study were State Civil Servant (ASN) of Regional Secretariat in Banjarnegara. The sampling technique in this study used is saturated sampling technique with a total sample of 112 ASN. Methods of data analysis using the Structural Equation Model (SEM) with analysis tools namely SmartPLS 3.0. The results of study indicate that psychological capital has a positive and significant influence on career commitment and also positive and significant on subjective well-being and job satisfaction. In addition, subjective well-being and job satisfaction also have a positive and significant effect on career commitment. Then, subjective well-being and job satisfaction mediate the effect of psychological capital on career commitment. Suggestions for the head of the department to hold training for work of an administrative nature in accordance with their position or duties and to create a pleasant work environment, for example, holding a State Civil Servant (ASN) gathering. If the State Civil Servant (ASN) is satisfied at work, then higher the career commitment will be.